Pengaruh Metode Shared Reading terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SD IT Al-Madani - Sari Ulandari; Lalu Parhanuddin; Muh. Yazid (Jurnal Eduforia: Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to determine the effect of the shared reading method on reading comprehension skills of fifth-grade students at SD IT Al-Madani. Reading comprehension remains a significant issue in Indonesian language learning, characterized by students’ difficulties in understanding text content, identifying main ideas, and drawing conclusions. This research used a quantitative approach with a one-group pretest–posttest experimental design. The sample consisted of 23 students. Data were collected through essay tests and analyzed using Shapiro-Wilk normality test and paired sample t-test. The results showed an increase in the mean score from 51.56 (pretest) to 68.61 (posttest). The t-test result indicated tcount 4.336 > ttable 1.717 at a significance level of 0.05. It can be concluded that the shared reading method significantly improves students’ reading comprehension skills by creating interactive and meaningful learning experiences.